Use of the JAK Inhibitor Ruxolitinib in the Treatment of Hemophagocytic Lymphohistiocytosis - Keenan, Camille; Nichols, Kim E.; Albeituni, Sabrin (Frontiers in Immunology, 2021)
Hemophagocytic lymphohistiocytosis (HLH) is a rare hyperinflammatory syndrome driven by overactive T cells and macrophages that abundantly secrete numerous pro-inflammatory cytokines, including interferon (IFN)-gamma, interleukin (IL)-1-beta, IL-2, IL-6, IL-10, IL-18, and tumor necrosis factor (TNF). The release of these and other cytokines underlies many of the clinical and pathologic manifestations of HLH, which if left untreated, can lead to multi-organ failure and death. The advent of etoposide-based regimens, such as the Histiocyte Society HLH-94 and HLH-2004 protocols, has substantially decreased the mortality associated with HLH. Nevertheless, the 5-year survival remains low at ~60%. To improve upon these results, studies have focused on the use of novel cytokine-directed therapies to dampen inflammation in HLH. Among the agents being tested is ruxolitinib, a potent inhibitor of the Janus Kinase (JAK) and Signal Transducer and Activation of Transcription (STAT) pathway, which functions downstream of many HLH-associated cytokines. Here, we review the basic biology of HLH, including the role of cytokines in disease pathogenesis, and discuss the use of ruxolitinib in the treatment of HLH.